Purchase Decisions For Beauty Products In Indonesia: The Role Of Word Of Mouth, Satisfaction, Trust, And Price - Tussi Sulistyowati; Hwihanus, Hwihanus (SEAN Institute, 2024)
This study investigates the factors that affect purchasing decisions for beauty products in Indonesia, utilising data collected from questionnaires administered to 102 respondents through Google Forms. By employing purposive sampling, the research ensures the relevance and reliability of the data, followed by rigorous validation and analysis using Structural Equation Modeling (SEM) with SmartPLS 4. The results suggest that traditional factors such as price and trust do not significantly impact customer satisfaction or purchasing behaviour. In contrast, while trust positively influences customer satisfaction, it does not directly lead to purchase decisions, and the mediating role played by customer satisfaction is minimal. Notably, the analysis reveals a significant moderating effect of word of mouth combined with price, suggesting that positive recommendations can enhance customer satisfaction even at higher price points. Based on these insights, beauty brands in Indonesia should prioritise improving product quality and implementing effective marketing strategies that emphasise perceived value. Building strong consumer trust and leveraging positive word-of-mouth through influencer partnerships can strengthen customer relationships in this competitive market.